Controlling Bone Graft Substitute Microstructure to Improve Bone Augmentation. Issue 13 (23rd May 2016) - Sheikh, Zeeshan; Drager, Justin; Zhang, Yu Ling; Abdallah, Mohamed‐Nur; Tamimi, Faleh; Barralet, Jake
Abstract : Vertical bone augmentation procedures are frequently carried out to allow successful placement of dental implants in otherwise atrophic ridges and represent one of the most common bone grafting procedures currently performed. Onlay autografting is one of the most prevalent and predictable techniques to achieve this; however, there are several well documented complications and drawbacks associated with it and synthetic alternatives are being sought. Monetite is a bioresorbable dicalcium phosphate with osteoconductive and osteoinductive potential that has been previously investigated for onlay bone grafting and it is routinely made by autoclaving brushite to simultaneously sterilize and phase convert. In this study, monetite disc‐shaped grafts are produced by both wet and dry heating methods which alter their physical properties such as porosity, surface area, and mechanical strength. Histological observations after 12 weeks of onlay grafting on rabbit calvaria reveal higher bone volume (38%) in autoclaved monetite grafts in comparison with the dry heated monetite grafts (26%). The vertical bone height gained is similar for both the types of monetite grafts (up to 3.2 mm). However, it is observed that the augmented bone height is greater in the lateral than the medial areas of both types of monetite grafts. It is also noted that the higher porosity of autoclaved monetite grafts increases the bioresorbability, whereas the dry heated monetite grafts having lower porosity but higher surface area resorb to a significantly lesser extent. This study provides information regarding two types of monetite onlay grafts prepared with different physical properties that can be further investigated for clinical vertical bone augmentation applications. Abstract : Onlay block grafting is used frequently for vertical bone augmentation for placing dental implants. In this study, two types of monetite grafts are prepared by wet and dry heating of brushite. The grafts are implanted on rabbit skulls and ≈3.2 mm of bone height gained with wet heat monetite having higher bone volume augmented than their dry heat counterparts.